Large Reversible Plasmon Shift with Au Nanodisc Dimers on Thin film VO2 - Bradley, Louise (My University, 2022)
By coupling Au dimer nanostructures to an underlying thin film of phase change material, vanadium dioxide, significant shifts in the plasmonic scattering spectra are observed, allowing for dynamic tuning within the visible spectral range.
Optica Advanced Photonics Congress 2022
Keywords: Nanostructures; vanadium dioxide; Thin films